Recent approaches and future trends for lignin-based materials - Dias, Otávio Augusto Titton [UNESP]; Negrão, Djanira Rodrigues [UNESP]; Gonçalves, Daniele Fernanda Chiarelli [UNESP]; Cesarino, Ivana [UNESP]; Leão, Alcides Lopes [UNESP] (My University, 2017)
Known as the main source of aromatic compounds in nature, lignin possesses heterogeneous composition which has high potential to be used in many industrial purposes. Lignin has been used as retardants of fire, thermal stabilizer, hydrophobicity agent, carbon fiber, aerogels and antioxidants. This review summarizes several uses of lignin-based components and their potential applications. We focused on the industrial uses of lignin in order to diminish the dependence of petroleum-based materials.
Keywords: Applications; biomaterial; biopolymer; lignin; properties